1971
DOI: 10.1143/ptp.46.1644
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Decay in Flight of a New Type Particle

Abstract: Among the secondary particles produced in a high energy jet shower and observed by emulsion chambers exposed to cosmic rays, a possible decay in flight of a new type particle was found.A new type of emulsion chamber!) with local producing layer of jet shower was designed in order to investigate super high energy jet showers in full detail by combining information about secondary charged particles at or near an origin of jet shower as well as r rays. Exposure of new type chambers for about 500 hours at about 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(105 citation statements)
references
References 0 publications
1
100
0
2
Order By: Relevance
“…Emulsion technology, pure nuclear emulsion and Emulsion Cloud Chamber (ECC) targets, has already demonstrated that it is a superb technique for the study of decay topologies [425][426][427][428][429][430][431]. A discussion of the performance that has been achieved in previous emulsion-based experiments is beyond the scope of this section.…”
Section: Emulsion Detectormentioning
confidence: 99%
“…Emulsion technology, pure nuclear emulsion and Emulsion Cloud Chamber (ECC) targets, has already demonstrated that it is a superb technique for the study of decay topologies [425][426][427][428][429][430][431]. A discussion of the performance that has been achieved in previous emulsion-based experiments is beyond the scope of this section.…”
Section: Emulsion Detectormentioning
confidence: 99%
“…Parity and angular momentum conservation force the ( j q = 1/2) states to decay to the ground states via FIGURE 1. First charm candidate event in nuclear emulsions [5]. Figure from Ref.…”
Section: Heavy-light Quark Spectroscopy the Global Picturementioning
confidence: 99%
“…Although one long-lived event in cosmic rays [21] predated the observation of the J/ψ, it was the observation of the J/ψ in both hadronic and e + e − interactions that led to the wide acceptance of charm. The hadroproduction resulted in e + e − pairs seen in the experiment of Sam Ting and his group at Brookhaven.…”
Section: Observations Of Charmmentioning
confidence: 99%